Experimental and numerical study of steel wire mesh reinforced G-HPC slab protected by UHMWPE FRC under multiple blast loadings. (15th January 2023) - Yuan, Pengcheng; Xiang, Hui; Xu, Shenchun; Liu, Jian; Su, Yu; Qu, Kefo; Wu, Chengqing
Highlights: This study explored the steel wire mesh (SWM) reinforced geopolymer based ultra-high performance concrete (G-UHPC) slabs protected by ultra-high molecular weight polyethylene (UHMWPE) fiber reinforced cloth (FRC) against multiple blast loadings. The SWM reinforced G-UHPC slab protected by UHMWPE FRC deformed plastically with the generation of few ejecting fragments, demonstrating superior multiple blast loading resistance. The SWM reinforced G-UHPC slab exhibited superior resistance against multiple blast loadings as compared to the plain G-UHPC slab. A finite element model was developed and validated by comparing the numerical results with the experimental data. A parametric study to supplement the experimental data and further reveal the blast-resistant mechanism of the slabs. Abstract: Engineering structures may experience multiple blast loadings owing to accidental explosions and terrorist attacks, however, few studies focused on the multiple blast loading effect on the structures. In this study, the multiple blast resistance of the steel wire mesh (SWM) reinforced geopolymer based high performance concrete (G-HPC) slabs protected by ultra-high molecular weight polyethylene (UHMWPE) fiber reinforced cloth (FRC) were investigated by experimental and numerical studies. The effects of the thickness and location of UHMWPE FRC on the multiple blast behavior of the SWM reinforced G-HPC slab were examined by parametric analysis. The failure modes and the blast-resistant mechanism of the slabs were revealed. The experimental results indicated that the SWM reinforced G-HPC slab exhibited superior resistance against multiple blast loadings as compared to the plain G-HPC slab. The SWM reinforced G-HPC slab protected by UHMWPE FRC has better multiple blast resistance, and the UHMWPE FRC effectively mitigated the blast loading and further reduced the damage to the slab. In addition, the findings of the parametric analysis revealed that UHMWPE FRC was more effective to enhance the blast resistance of a slab as it was placed on the bottom surface.